Human T cells express CD25 and Foxp3 upon activation and exhibit effector/memory phenotypes without any regulatory/suppressor function - Kmieciak, Maciej (BioMed Central, 2009)
BACKGROUND: Foxp3 has been suggested to be a standard marker for murine Tregs whereas its role as marker for human Tregs is controversial. While some reports have shown that human Foxp3+ T cells had no regulatory function others have shown their role in the inhibition of T cell proliferation. METHODS: T cell activation was performed by means of brayostatin-1/ionomycin (B/I), mixed lymphocyte reaction (MLR), and CD3/CD28 activation. T cell proliferation was performed using BrdU and CFSE staining. Flow cytometry was performed to determine Foxp3 expression, cell proliferation, viabilities and phenotype analyses of T cells. RESULTS: Both CD4+ and CD8+ T cells expressed Foxp3 upon activation in vitro. Expression of Foxp3 remained more stable in CD4+CD25+ T cells compared to that in CD8+CD25+ T cells. The CD4+CD25+Foxp3+ T cells expressed CD44 and CD62L, showing their effector and memory phenotypes. Both FoxP3- responder T cells and CD4+FoxP3+ T cells underwent proliferation upon CD3/CD28 activation. CONCLUSION: Expression of Foxp3 does not necessarily convey regulatory function in human CD4+CD25+ T cells. Increased FoxP3 on CD44+ effector and CD44+CD62L+ memory T cells upon stimulation suggest the activation-induced regulation of FoxP3 expression.